World Trade Organization and Its Impact on India: विश्व व्यापार संगठन और भारत पर इसका प्रभाव - Sharma, Jagriti (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
India's purist approach toward a multilateral trade system—a fair, open, transparent, and balanced trade framework—has always aligned with the interests of developing nations and has consistently been reflected in World Trade Organization (WTO) negotiations. India has also opposed the expansion of trade rules into areas such as labor standards, competition policy, government procurement, trade in investment, and the Trade Facilitation Agreement. Furthermore, India has raised its voice against rules that favor developed countries while disadvantaging developing and underdeveloped nations. The numerous regulations proposed by the WTO, along with the various cases filed against India, have had a negative impact on the country. However, as an international organization monitoring global trade and trade practices, the WTO does, to some extent, safeguard the interests of developing and non-developing nations. Abstract in Hindi Language: बहुपक्षीय व्यापार प्रणाली के प्रति भारत का शुद्धतावादी दृष्टिकोण-एक निष्पक्ष, खुली, पारदर्शी और संतुलित व्यापार व्यवस्था विकासशील देशों के हित में थी और यह हमेशा विश्व व्यापार संगठन वार्ताओं में बनी रही है। भारत श्रम मानकों, प्रतिस्पर्धा नीति, सरकारी खरीद, निवेश में व्यापार और व्यापार सुविधा समझौते जैसे क्षेत्रों में व्यापार नियमों के विस्तार का भी विरोध करता रहा है। भारत ने उन नियमों के खिलाफ भी आवाज उठाई है जो विकासशील देशों के पक्ष में हैं और विकासशील और अविकसित देशों के पक्ष में नहीं हैं। विश्व व्यापार संगठन द्वारा प्रस्तावित बहुत से नियमों और उसके खिलाफ चल रहे कई मामलों का भी भारत पर नकारात्मक प्रभाव पड़ा है। लेकिन, विश्व व्यापार और व्यापार प्रथाओं पर नजर रखने वाली एक अंतरराष्ट्रीय संस्था होने के नाते विश्व व्यापार संगठन कुछ हद तक विकासशील और गैर-विकासशील देशों के हितों की रक्षा करती है। Keywords: भारत, विश्व व्यापार संगठन, विश्व व्यापार, अर्थव्यवस्था, प्रभाव।